Toward Evidence-Based Practice. Issue 5 (September 2020) - Rohan, Annie J.; Krowchuk, Heidi V.; Lake, Eileen T.; Roth, Cheryl K.
Abstract : Experts suggest how 6 research articles can be used in nursing practice.